Seemingly Harmless Differentiated Thyroid Carcinoma Presenting as Bone Metastasis - D. Magalhães; C. Costa; I. Furtado; M. J. Matos; A. P. Santos; H. Duarte; M. Afonso; J. Lobo; I. Torres (Case Reports in Endocrinology)
Thyroid carcinoma is the most common endocrine neoplasia. Differentiated thyroid carcinomas (DTCs) represent the majority of cases, which usually follow an indolent clinical course with low mortality rates. The authors describe two cases of well DTC without classic histological poor prognosis features, presenting as extensive and unresectable osteolytic bone metastases. DTCs are considered harmless tumours, due to their benign and silent behaviour. The authors want to underline the importance of clinical awareness during follow-up in cases of DTC, which can be aggressive in presentation and behaviour. Timely identification and diagnosis of these tumours are essential for prompt treatment initiation and improvement of overall survival.